BREXIT IMPACT ON THE EU’S CLIMATE DIPLOMACY - William Sulisyo; Hendhia; Ivonne; Ellica; Andhika Raflie; Grace Miss Hutabarat (Sociae Polites, 2020)
European Union is a political and economic union of 27 member states. Britain is one of the leading members of the EU. The UK decided to leave the European Union. The EU struggled with the project that was being worked on called Climate Diplomacy. EU and its member states are part of the United Nations Framework Convention on Climate Change (UNFCCC). The EU has built a significant and potentially a leading position in global governance on climate. Brexit is only one factor that could change the dynamics of its role. In this case, The EU has a negative impact as well as positive impacts due to Brexit. It turns out that the negative implications are more dominant than positive effects. European Union will lose the financial contribution made by the UK to the EU budget. Keywords: European Union, UK, Brexit, Climate Diplomacy.